Adaptation of Fintech as a Means of Collecting Islamic Philanthropic Funds; Analysis of Legal Principles - Hilmi Ridho; Imam Malik Riduan; Khoirul Anwar; Muhammad Yunus (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
The development of financial technology (fintech) has significantly transformed financial transactions from cash-based to non-cash systems. In Indonesia, the widespread use of technology highlights the growing importance of fintech across various sectors, including the collection of Islamic philanthropic funds such as Zakat, Infak, and Sedekah (ZIS). This study aims to analyze the payment of ZIS funds through digital platforms from the perspective of applicable legal principles. It also examines the legal status of zakat on money in Islamic law and the permissibility of paying zakat in monetary form. This research employs a normative legal method using conceptual and historical approaches, analyzed through deductive reasoning. The findings indicate that the majority of Islamic scholars and religious institutions agree on the obligation of zakat on money once its value reaches the nisab equivalent to gold or silver and fulfills the haul requirement. This view is based on the role of money as the primary indicator of wealth in the modern era. Hadiths that mention zakat obligations in the form of livestock or agricultural products are interpreted as referring to the value (qīmah) rather than the physical object (`ain). Furthermore, the use of fintech in ZIS fund collection is considered permissible as long as it complies with Sharia principles and avoids harmful elements. Digital technology in ZIS collection aligns with the principle of ḥifẓ al-māl (protection of wealth) by enhancing efficiency and expanding outreach. In cases of failed online zakat transactions, responsibility is determined based on negligence by the muzaki, zakat institution, or service provider. Such failures do not nullify the zakat obligation, which remains the responsibility of the muzaki to fulfill.